Visit of Prime Minister Dr. Manmohan Singh to Kuala Lumpur for the India-ASEAN Summit, 11-14 December 2005. - Manmohan Singh 1932-; India. External Publicity Division; India-ASEAN Business Summit 2005 Kuala Lumpur, Malaysia); East Asia Summit 2005 Kuala Lumpur, Malaysia). (New Delhi External Publicity Division, Ministry of External Affairs, 2005)
Includes report of the First East Asia Summit held on 13-14 December 2005 in Kuala Lumpur, Malaysia.
Keywords: Manmohan Singh -- 1932- -- Travel -- Malaysia -- Kuala Lumpur -- Congresses; India -- Foreign relations -- Southeast Asia -- Congresses; Southeast Asia -- Foreign relations -- India -- Congresses; Southeast Asia -- Economic integration -- Congresses; India -- Foreign relations -- East Asia -- Congresses; East Asia -- Foreign relations -- India -- Congresses